Biomarkers for Pediatric Pulmonary Arterial Hypertension – A Call to Collaborate - Colvin, Kelley L.; Dufva, Melanie J.; Delaney, Ryan P.; Ivy, D D.; Stenmark, Kurt R.; Yeager, Michael E. (Frontiers in Pediatrics, 2014)
Therapeutic approaches in pediatric pulmonary arterial hypertension (PAH) are based primarily on clinician experience, in contrast to the evidence-based approach in adults with pulmonary hypertension. There is a clear and present need for noninvasive and objective biomarkers to guide the accurate diagnosis, treatment, and prognosis of this disease in children. The multifaceted spectrum of disease, clinical presentation, and association with other diseases makes this a formidable challenge. However, as more progress is being made in the understanding and management of adult PAH, the potential to apply this knowledge to children has never been greater. This review explores the state of the art with regard to noninvasive biomarkers in PAH, with an eye towards those adult PAH biomarkers potentially suitable for application in pediatric PAH.